2017
DOI: 10.1016/j.jenvp.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

“I feel it is mine!” – Psychological ownership in relation to natural resources

Abstract: The use of natural resources often generates conflict among stakeholders. Conflict analysis and management in this sector has traditionally been based on compliance enforcement and/or education. Recently, however, the need for alternative approaches has been increasingly highlighted. In this study, we address the need for in-depth analysis, and introduce the theoretical concept of psychological ownership to improve the understanding and potential management of conflict situations. We suggest that ownership fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 82 publications
0
31
0
1
Order By: Relevance
“…People who exhibit high psychological ownership of nature are motivated to engage in responsible behavior and protect, maintain, care for, and possibly even defend their possessions when necessary (Potdar et al, 2018). Prior research on psychological ownership in the context of natural resource management has found that psychological ownership reduces conflicts in natural resource exploitation and forms a cooperative relationship that is conducive to the sustainable development of the natural environment (Matilainen et al, 2017). In addition, endowment effect theory indicates that, aside from improving the individual’s sense of possession and emotional connection to the possession, psychological ownership increases the individual’s degree of sensitivity and pain in response to the loss of the possession, thus prompting the individual to take loss avoidance measures (Carmon and Ariely, 2000).…”
Section: The Mediating Effect Of Psychological Ownershipmentioning
confidence: 99%
“…People who exhibit high psychological ownership of nature are motivated to engage in responsible behavior and protect, maintain, care for, and possibly even defend their possessions when necessary (Potdar et al, 2018). Prior research on psychological ownership in the context of natural resource management has found that psychological ownership reduces conflicts in natural resource exploitation and forms a cooperative relationship that is conducive to the sustainable development of the natural environment (Matilainen et al, 2017). In addition, endowment effect theory indicates that, aside from improving the individual’s sense of possession and emotional connection to the possession, psychological ownership increases the individual’s degree of sensitivity and pain in response to the loss of the possession, thus prompting the individual to take loss avoidance measures (Carmon and Ariely, 2000).…”
Section: The Mediating Effect Of Psychological Ownershipmentioning
confidence: 99%
“…The terminology of ownership has been widely explained in possessive tendencies and the perspective of mind [39][40][41]. Previous studies on ownership have explored various explanations concerning the relationship of ownership and impact on job satisfaction, commitment, intent to stay or citizenship behaviour [42][43][44][45][46][47][48][49]. Hence, it is a must to understand how the sense of ownership of an individual is developed.…”
Section: Sense Of Ownershipmentioning
confidence: 99%
“…Karahanna, Xu, & Zhang, 2015), idea adoption (Baer & Brown, 2012), to management of natural resources (e.g. Matilainen, Pohja-Mykrä, Lähdesmäki, & Kurki, 2017). People can even develop psychological ownership to an object only by imagining that they touch that object (Peck et al 2013).…”
Section: For Reviews)mentioning
confidence: 99%
“…Each of these mechanisms allows for the development of feelings of possession of a target object, but from different points of departure. According to Pierce and colleagues (2003), people can develop strong feelings of psychological ownership when one of these mechanisms is activated, but that possessive feelings are usually stronger when triggered by multiple mechanisms at once (see also Matilainen et al, 2017).…”
Section: For Reviews)mentioning
confidence: 99%